Genome-Wide Association Studies Provide Insights into the Genetic Determination of Flower and Leaf Traits of Actinidia eriantha - Liao, Guanglian; Zhong, Min; Jiang, Zhiqiang; Tao, Junjie; Jia, Dongfeng; Qu, Xueyan; Huang, Chunhui; Liu, Qing; Xu, Xiaobiao (Frontiers in Plant Science, 2021)
Kiwifruit (Actinidia eriantha) is a dioecious vine, the pollen of male cultivars has a direct effect on the fruit quality. To facilitate molecular breeding and gene identification, here we have performed genome-wide association studies (GWAS) on eleven traits of flower and leaf. A total of 946,337 highly consistent SNP markers were obtained which throughout the whole genome. Phylogenetic tree analysis and population structure analysis showed that the 143 germplasms can be divided into two groups. The linkage disequilibrium analysis showed that A eriantha have a relatively fast attenuation rate, and the average attenuation distance of LD was 0.1-0.3 Kb. MLM (QK) model was been determined as the best model for correlation analysis, eight and three SNPs were associated with flower and leaf related traits were identified, respectively, at 0.01 significance level. However, SNPs markers associated with stamen number per flower, pollen viability, total chlorophyll content and total flavonoid content were not identified at 0.01 significant level. But it's worth noting that they were but one, one, five and two SNPs were identified associated with these traits at 0.05 significant level, respectively. Our study provides insights into the complex flower and leaf related biology and identifies genes controlling important traits in A. eriantha through GWAS, which extends the genetic resources and basis for facilitating molecular breeding in kiwifruit.